Efficiency Analysis of Self-Estimated Pricing at PTPN I Regional 7 Using a Multi-Channel Model - Prasetiyo, Muhammad Khoirul; Zakaria, La (Transcendent Journal of Mathematics and Applications, 2025)
This study analyzes the efficiency of the Self-Estimate Price (HPS) process in the Analysis and Finance Division of PT Perkebunan Nusantara I Regional 7 after the organizational restructuring in April 2024. The restructuring led to the separation of PT Perkebunan Nusantara I and IV Regional 7, affecting the number of staff handling the HPS process. The research uses the Multi-Channel Single-Phase queuing model with Poisson arrival distribution and exponential service time, based on data collected from April to December 2024. Unlike previous studies using data before the restructuring and involving three servers (Dita Arfi, 2024), this study focuses on two servers in the new organizational context. The results show significant inefficiencies, including a system utilization rate of 0.8, a probability of no customers in the system of 11.1%, and an average queue length of 2.84 packages. Additionally, the average waiting time in the queue is 5 days, and the total time in the system is 8 days. The study concludes that workload imbalance and limited human resources are the leading causes of inefficiency, and recommends redistributing tasks or adding staff to improve efficiency. This research provides a new perspective on post-restructuring efficiency.